2012
DOI: 10.1530/erc-11-0140
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of large parathyroid adenomas

Abstract: In this study, we genetically characterized parathyroid adenomas with large glandular weights, for which independent observations suggest pronounced clinical manifestations. Large parathyroid adenomas (LPTAs) were defined as the 5% largest sporadic parathyroid adenomas identified among the 590 cases operated in our institution during 2005–2009. The LPTA group showed a higher relative number of male cases and significantly higher levels of total plasma and ionized serum calcium (P<0.001). Further analysis of 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 66 publications
1
48
0
2
Order By: Relevance
“…This MEN1 intragenic mutation frequency of ~11% is in agreement with earlier literature, which found a range between 12-20% [11][12][13], and contrasts with recent suggestions that the frequency might be considerably higher (up to 35-40%) [8,9,[17][18][19][20]. No mutations in genes recently proposed to be implicated in parathyroid adenoma tumorigenesis, such as CTTNB1, EZH2 and POT1, were identified, attesting to the rarity of these candidate genes' potential contributions [21].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This MEN1 intragenic mutation frequency of ~11% is in agreement with earlier literature, which found a range between 12-20% [11][12][13], and contrasts with recent suggestions that the frequency might be considerably higher (up to 35-40%) [8,9,[17][18][19][20]. No mutations in genes recently proposed to be implicated in parathyroid adenoma tumorigenesis, such as CTTNB1, EZH2 and POT1, were identified, attesting to the rarity of these candidate genes' potential contributions [21].…”
Section: Resultssupporting
confidence: 89%
“…However, these derangements occur, collectively, in a minority of these tumors [2,3,7], and even when present are likely to cooperate with other driver lesions; thus multiple additional targets for tumorigenic mutation and future therapeutics undoubtedly exist. Indeed, studies of the genomes of parathyroid adenomas using a variety of methods have revealed a complex and heterogeneous landscape of chromosomal and DNA sequence level changes [8][9][10][11][12][13]. Identification of novel, recurrently altered genes has been difficult due to a low frequency of mutation observed in candidate genes and the limited number of cases examined [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…3 Indeed, in a study published by Sulaiman et al in 2012, the genetic characterisation of sporadic parathyroid adenomas weighing >4g revealed specific genomic features that correlated positively with PTH levels and therefore parathyroid hyperfunction. 4 The present case was that of a true giant parathyroid adenoma, both in terms of its size and weight, associated with severe hypercalcaemia and extremely high PTH levels. These features raised the suspicion of malignancy and necessitated urgent surgery.…”
Section: 3mentioning
confidence: 82%
“…Moreover Sulaiman and cols. showed that most of larger parathyroid lesions were benign PAs associated with specific genomic features (32).…”
Section: Discussionmentioning
confidence: 99%